THE ROLE OF GOVERNMENT SUPPORT FOR THE FULL USE OF PRODUCTION CAPACITIES CREATED IN ENTERPRISES (World Economics and Finance Bulletin, 2022)
The article scientifically analyzes the role and directions of state support for the full use of production capacities created in recent years at enterprises
Keywords: Production capacities; investments; government support; investment projects